Volatility Spillover and Investor Sentiment: Subprime Crisis - Mouna Abdelhédi-Zouch,; Mouna Boujelbène Abbes,; Younès Boujelbène, (Asian Academy of Management Journal of Accounting and Finance, 2015)
In this paper, we test the role of the American investor sentiment in the amplification of the subprime financial crisis by examining the volatility spillover between the Standard & Poor's 500 Index (S&P 500) returns and investor sentiment measures. We show a significant effect of investor sentiment variation on return and volatilities, and we reveal the contribution of returns shocks to the variability of investor sentiment variation during the subprime crisis. Moreover, we notice the determinant role of investor sentiment in the amplification of the subprime financial crisis by the intense spillover of volatility from investor sentiment to returns. Our finding indicates that investors can use investor sentiment as an indicator to predict returns-volatility.